Olahraga Tradisional Menyipet Dan Balogo Di Masyarakat Kota Palangka Raya - Abd Rahaman Azahari (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2016)
Implications of the study as follows: reviewed from the aspects of social action, so the results of this study reinforce the theory of action Parsons, that "all social actions undertaken by traditional sports players, municipalities, students and teachers in the town of Palangka Raya in traditional sports menyipet and balogo always base to a predetermined goal, which is to achieve the feat in Isen Mulang cultural festival held once a year throughout Central Kalimantan province. Reviewed from Max Weber's theory of social action and symbolic interactionist theory Hebert Mead, the results of this study reinforce the view of Weber and Mead, that anyaction by individuals or groups always thought positive and negative aspects that will occur from the action, and the ability to predict for the futuret, although in a simple form, in accordance with the level of knowledge. Reviewed from the symbolic interactionist theory, the results of this study reinforce the view Mead, that the city of Palangka Raya society action in the process of developing and preserving traditional sports ofmanyipet andbalogo was greatly influenced by the reality on the field and logical thinking ahead about the traditional sports and the interaction between them in the environment or society.phenomenological theory is always traying to understand the culture through cultural view of the owner or the culprit. There are three cultural phenomenon they are ideas,activities and artifact.Those cultural phenomenon if the noteon a line to the three states of culture as contained in the definition of culture Koentjaraningrat. Ideas is equal to the system of ideas,activities isequal to the action,and the last is artifact which identical with the human work.